Russia`s Participation in the European Convention for the Protection of Human Rights and Fundamental Freedoms - A. Y. Novoseltsev; K. V. Stepanyugin (Московский журнал международного права, 2021)
INTRODUCTION. The article examines problematic issues of Russia’s participation in the European Convention for the Protection of Human Rights and Fundamental Freedoms. According to the authors, the form of Russia’s participation in the Convention, associated with membership in the council of Europe, is unacceptable for its sovereignty. When ratifying the Convention, the degree of objectivity and impartiality of the ECHR in relation to the Russian Federation and the properties of the legal norms of the Convention were not taken into account.MATERIALS AND METHODS. The materials for the research are international agreements, resolutions of international organizations, decisions of the ECHR and the Constitutional Court of the Russian Federa- tion, as well as doctrinal sources on the topic. The methodological basis of the article was formed by general scientific and special research methods. The article critically analyzes the arguments in favor of Russia’s participation in the European Convention and examines the reasons why the ECHR can hardly be called an objective court for a country that is not a member of the EU.RESEARCH RESULTS. The authors believe that the unenforceability of ECHR judgements is only part of the problem of enforcing binding decisions of international organizations. According to the authors, it is necessary to determine the fundamental foundations of Russia’s participation in international organizations that can make decisions legally binding for our country, and to limit their circle to the participants of the integration association with Russia, organizations of strategic partners, as well as organizations in which Russia can influence the adoption decisions. The principles of Russia’s participation in international organizations that make legally binding decisions should be included in the Federal Law “On International Treaties of the Russian Federation”.DISCUSSION AND CONCLUSIONS. The subordination of Russia to the jurisdiction of an interstate human rights body must meet a number of conditions that the ECHR does not meet. Because of this, problems arise with the implementation by Russia of the decisions of the ECHR. The authors share the point of view that the ECHR is an effective mechanism for the protection of rights and freedoms, but only for a group of states – European integration participants bound by common interests, values, and coordinated foreign and domestic policies. Therefore Russia needs to return to the rules of cooperation in the field of human rights with European states, set out in the Helsinki Final Act on Security and Cooperation in Europe.